IDENTIFIKASI METODE PADA PERANCANGAN SISTEM INFORMASI MANAJEMEN PANTI ASUHAN : Systematic Literature Review - Erba Lutfina; M. Zakki Abdillah; Cicilia Yolisday; Ahmad Nugroho (Fakultas Sains dan Teknologi, Universitas Nasional Karangturi, 2023)
The manual management system that is still implemented at the Orphanage can result in an inefficient management system such as collisions in visiting schedules, the effectiveness of data is not organized, and the target of assistance is not distributed as needed. There are various ways to overcome schedule collisions, reduce data access time and costs and improve management performance, one of which is by designing a Management Information System. The purpose of this research is to identify a method for designing an orphanage management system using the Systematic Literature Review (SLR) method, the data of which was obtained from the relevant journals in 2017–2021. The Systematic Literature Review (SLR) method can be useful for researchers and practitioners, for researchers this research will help them to see the accuracy of methods that are appropriate for use in making Management Information Systems at Orphanages. From the research results, it was found that the relevant years for conducting research related to management systems in orphanages were 2021 and 2019. From the research results, it was found that the system development method most often used was the Waterfall method with a testing method using the black box method.